Factors of Value Chain Affect Bank Efficiency - Trung Kim Quoc Nguyen (Ital Publication, 2023)
This paper aims to determine and estimate the factors in the value chain that affect the efficiency of state-owned commercial banks in Vietnam. The study employs a combination of qualitative techniques, such as conducting interviews with top executives, financial managers, chief accountants, and employee surveys, along with quantitative methods like ordinary least squares analysis. The outcomes reveal four critical segments within the value chain – the retail department, operation department, back office, and call center – all of which significantly influence the efficiency of the banks. Additionally, drawing upon value chain theory and Porter's model (1985), the author underscores the significance of implementing a robust value chain strategy. This strategic approach has the potential to substantially enhance the competitive advantages of state-owned commercial banks in Vietnam. Doi: 10.28991/ESJ-2023-07-06-010 Full Text: PDF